Left-dislocation in Republican Latin. - Hilla Halla-Aho (Amsterdam Studies in Classical Philology, 2018)
In the construction known as left-dislocation, an element appears in a fronted position, before the clause to which it belongs, usually introducing the topic of the sentence. Based on a detailed analysis of syntax, information structure and pragmatic organization, this study explores how left-dislocation is used in republican Latin comedy, prose and inscriptions as a device to introduce topics or other pragmatically prominent elements. Taking into consideration especially relative clause syntax and constraints of each text type, Hilla Halla-aho shows that, in the context of early Latin syntax and the evolving standards of the written language, left-dislocation performs similar functions in dramatic dialogue, legal inscriptions and archaic prose.